Estudo de reconciliação operativa da sondagem na lavra subterrânea na mina do São Chico (Província Tapajós): relatório de estágio profissional geologia de mina Serabi-Gold - PAIVA, Isabella dos Santos (2024)
Professional internships are recommended to students for professional experience and integration of knowledge acquired in the classroom. The São Chico mine (site of the internship) is located in the Tapajós River valley, about 220 km south of the city of Itaituba, in the State of Pará. Among the activities developed, a drilling chamber was programmed and executed in one of the veins of the São Chico mine, in order to obtain a comparative analysis between the actual and estimated production of the drilling, taking into account some geomechanical parameters such as advance and recovery, assessment of the degree of fracturing and RQD of the cores. The execution of the activities linked to the drilling was based consecutively on: Consultation of the company's database to schedule the holes to be drilled, use of software for planning the squares in the chambers in which the drills will be installed, geological mapping of the drilled holes , geotechnical classification (RQD) of drill cores, feeding the database and geological interpretation, and finally, the analysis of the results. The best overall RQD percentage result was given to hole 22-SCUD-649 (Table 3), whose lowest calculated percentage value corresponds to 91%, while the worst overall performance corresponds to hole 22-SCUD-651 (Table 5), in which no maneuver achieved 100% RQD in a hole just 20 meters long. In relation to just the maneuver, the worst overall percentage refers to 25% corresponding to hole 22- SCUD-651 A (Table 6) with 51.20 meters of drilled material. Referring to the number of fractures, the hole that presented the lowest result of fractured material was the 22-SCUD 653 with 29 fractures distributed in only 16.50 meters of material, followed by 31 fractures in 43.40 meters of the 22-SCUD -649 and of material while the hole with the highest number of fractures corresponds to 22-SCUD-650 (Table 4) with a total of 89 fractures along 68.15 meters of core, followed by 22-SCUD-653 A (Table 8 ) with 69 fractures in 68 meters of material. The results of the drilled holes allowed a comparative geomechanical reading in which only the SCUD-649 and SCUD-650 presented an excellent degree of rock quality (RQD) with an average of 98.4% and 94% respectively, while the SCUDS 651 A (average of 89.8 %), SCUD 653 (average of 85.2%) and SCUD 653 A (average of 84.4%) had good RQD quality and only the regular SCUD 651 with 67.7%. The result of the RQD quality grade reflected in the operative success in which of the six drilled holes, four reached or came close to the desired depth, without interruptions (22-SCUD-649, 22-SCUD-650, 22-SCUD-651A and 22- SCUD-653A). Therefore, from a geomechanical point of view, the operational scenario discussed in this report proved to be advantageous, however, further studies are necessary, such as the possibility of the existence of parallel veins or pockets that reconcile the operational viability of future projects at the same level.